2018
DOI: 10.3389/fimmu.2018.00814
|View full text |Cite
|
Sign up to set email alerts
|

Tribody [(HER2)2xCD16] Is More Effective Than Trastuzumab in Enhancing γδ T Cell and Natural Killer Cell Cytotoxicity Against HER2-Expressing Cancer Cells

Abstract: An enhanced expression of human epidermal growth factor receptor 2 (HER2, ErbB2) often occurs in an advanced stage of breast, ovarian, gastric or esophageal cancer, and pancreatic ductal adenocarcinoma (PDAC). Commonly, HER2 expression is associated with poor clinical outcome or chemoresistance in ovarian and breast cancer patients. Treatment with humanized anti-HER2 monoclonal antibodies, such as trastuzumab or pertuzumab, has improved the outcome of patients with HER2-positive metastatic gastric or breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 74 publications
0
80
0
1
Order By: Relevance
“…Recently, we reported that the application of bsscFv [HER2xCD3] and tribody [(HER2) 2 xVγ9] enhanced the granzyme B release of PBL‐derived T cells of healthy donors and pancreatic cancer patients, whereas the intracellular expression of granzyme B was nearly comparable in unstimulated versus bsAb‐activated cells . By comparing the intracellular granzyme A and B expression of ex vivo isolated PBL versus TIL of ovarian cancer patients without stimulation, we observed an enhanced production of both cytotoxic mediators in CD8‐TIL compared to CD8‐PBL, whereas the production in Vδ1 and Vδ2 T cells was similar in PBL and TIL suggesting that γδ T cells in the analyzed ovarian cancer patients are in an pre‐activated stage.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, we reported that the application of bsscFv [HER2xCD3] and tribody [(HER2) 2 xVγ9] enhanced the granzyme B release of PBL‐derived T cells of healthy donors and pancreatic cancer patients, whereas the intracellular expression of granzyme B was nearly comparable in unstimulated versus bsAb‐activated cells . By comparing the intracellular granzyme A and B expression of ex vivo isolated PBL versus TIL of ovarian cancer patients without stimulation, we observed an enhanced production of both cytotoxic mediators in CD8‐TIL compared to CD8‐PBL, whereas the production in Vδ1 and Vδ2 T cells was similar in PBL and TIL suggesting that γδ T cells in the analyzed ovarian cancer patients are in an pre‐activated stage.…”
Section: Discussionmentioning
confidence: 92%
“…We applied tumor cells initially generated out of the tumor from patient OC11, which revealed an intermediate cisplatin response (Fig. 3) and a high expression of HER‐2 . We cocultured these tumor cells with autologous PBL or TIL ex vivo isolated from patient OC11 after adjuvant therapy followed by three further cycles with carboplatin/paclitaxel and a relapse of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another effective strategy to improve NK cell ADCC is incorporation of Trastuzumab in the bispecific antibody format (discussed below). Bispecific Trastuzumab antibody [(HER2)2xCD16] significantly enhanced ADCC compared to Trastuzumab treatment (214).…”
Section: Nct02240706 Nct02632721mentioning
confidence: 99%
“…Для сравнения цитотоксичность направленных токсинов также измеряли с использованием линий клеток с различным содержанием рецептора ERBB2. Использовали линии клеток BT474 и SCOV3 с высоким количеством рецептора ERBB2, линии клеток HEK293 и AsPc1 с низким количеством рецептора ERBB2 и клетки RAJI, на поверхности которых рецептор практически отсутствует [9]. Тестирование направленных токсинов проводили путём добавления токсинов в лунки с клетками с последующей инкубацией в течение 5 дней.…”
unclassified